A Grounded Theory Study of Determinants of Access to MEPs for Human Rights NGOs regarding the Human Rights Situation in Iran - Abdollah Baei Lashaki‬; Alberto Lanzavecchia (حقوق بشر)
The EP has become an essential venue for Human Rights NGOs who work on Iran's human rights issues. However, the determinants of their access to MEPs are not precise. This study aimed to generate a theory grounded on the data that explains the determinants of access to MEPs for HRNGOs regarding the human rights issues in Iran. The systematic design of grounded theory designed by Corbin and Strauss is applied in this study. Theoretical sampling guided the recruitment of 11 representatives of Human Rights NGOs covering the human rights issues in Iran. Continuous comparison method in three phases of open, axial and selective coding was operated for data analysis. The theory of informational determinants of access of Human Rights NGOs to MEPs explains the determinant of access of these organisations to MEPs. The generated theory can guide Human Rights NGOs to apply the best strategy to access MEPs on human rights issues.